Economic viability in feedlot cattle with traceability - Costa, Tiago Eid [UNESP] (2019)
This research analyzed the economic viability of the implementation of the TRACES List as traceability in cattle confinement system. Traceability in agricultural production is a growing demand from consumer markets around the world, whose investment may represent an opportunity for value creation. A feedlot cattle with rotation of 7,500 animals / year was used in the state of São Paulo, Brazil, whose data were analyzed between 2014 and 2015, which is characterized as a unique case study and has a quantitative approach. Through the Discounted Cash Flow method it was found that investing in the Traces List allows the creation of economic value for producers, considering the incremental gain of 3.27% in the Internal Rate of Return, Positive Net Present Value and reduction investment payback (Discounted Payback) in 1 year. Thus, the results highlight the monetary increase with the implementation of the traceability feedlot cattle, which demonstrates that such system provides higher added value than the nontraceability feedlot cattle.